Selenomethionine Attenuated H2O2-Induced Oxidative Stress and Apoptosis by Nrf2 in Chicken Liver Cells - Lingyu Xie; Yibin Xu; Xiaoqing Ding; Kaixuan Li; Shuang Liang; Danlei Li; Yongxia Wang; Aikun Fu; Weixiang Yu; Xiuan Zhan (MDPI AG, 2023)
Earlier studies have shown that selenomethionine (SM) supplements in broiler breeders had higher deposition in eggs, further reduced the mortality of chicken embryos, and exerted a stronger antioxidant ability in offspring than sodium selenite (SS). Since previous studies also confirmed that Se deposition in eggs was positively correlated with maternal supplementation, this study aimed to directly investigate the antioxidant activities and underlying mechanisms of SS and SM on the chicken hepatocellular carcinoma cell line (LMH). The cytotoxicity results showed that the safe concentration of SM was up to 1000 ng/mL, while SS was 100 ng/mL. In Se treatments, both SS and SM significantly elevated mRNA stability and the protein synthesis rate of glutathione peroxidase (GPx) and thioredoxin reductase (TrxR), two Se-containing antioxidant enzymes. Furthermore, SM exerted protective effects in the H2O2-induced oxidant stress model by reducing free radicals (including ROS, MDA, and NO) and elevating the activities of antioxidative enzymes, which performed better than SS. Furthermore, the results showed that cotreatment with SM significantly induced apoptosis induced by H2O2 on elevating the content of Bcl-2 and decreasing caspase-3. Moreover, investigations of the mechanism revealed that SM might exert antioxidant effects on H2O2-induced LMHs by activating the Nrf2 pathway and enhancing the activities of major antioxidant selenoenzymes downstream. These findings provide evidence for the effectiveness of SM on ameliorating H2O2-induced oxidative impairment and suggest SM has the potential to be used in the prevention or adjuvant treatment of oxidative-related impairment in poultry feeds.